Reservoir dogs - Bender, Lawrence; Tarantino, Quentin; Keitel, Harvey; Roth, Tim.; Penn, Christopher; Buscemi, Steve, 1958-; Tierney, Lawrence, 1919-2002.; Madsen, Michael; Hellman, Monte, 1932-; Gladstein, Richard N.; Sekula, Andrzej; Rachtman, Karyn; et al. (Sana Monica, Calif. : Artisan Entertainment, 2002)
They were strangers, together to pull off the perfect jewel heist. Their simple robbery turns into a bloody ambush when they realize one of them is a police informant.
Includes widescreen and full screen versions.
Originally produced as a motion picture in 1992.
Special features: deleted scenes; interviews with cast and crew; a tribute to Lawrence Tierney; Reservoir dogs director tribute; The class of '92 (review of films presented at the 1992 Sundance Film Festival); Small dogs : action figure development documentary; Film noir web : the writers and directors behind the legacy of this classic genre; select scene commentary with cast, crew and critics; K-BILLY interactive radio; Reservoir dogs style guide; Securing the shot : location scouting with Billy Fox; original theatrical trailer; poster gallery.
Editor, Sally Menke ; director of photography, Andrzej Sekula ; music supervisor, Karyn Rachtman.
Harvey Keitel, Tim Roth, Chris Penn, Steve Buscemi, Lawrence Tierney, Michael Madsen.
DVD format; DTS digital surround sound; 5.1 Dolby digital audio; 2.0 Dolby digital audio.
Keywords: Jewel thieves -- Drama; Informers -- Drama